2017
DOI: 10.1371/journal.pone.0184615
|View full text |Cite
|
Sign up to set email alerts
|

Grape microbiome as a reliable and persistent signature of field origin and environmental conditions in Cannonau wine production

Abstract: Grape berries harbor a wide range of microbes originating from the vineyard environment, many of which are recognized for their role in the must fermentation process shaping wine quality. To better clarify the contribution of the microbiome of grape fruits during wine fermentation, we used high-throughput sequencing to identify bacterial and fungi communities associated with berries and musts of Cannonau. This is the most important cultivar-wine of Sardinia (Italy) where most vineyards are cultivated without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 60 publications
(91 reference statements)
6
77
0
3
Order By: Relevance
“…This observation suggests that each vineyard has fungal species which are the potential fungal signature of that region. Our result is in agreement with previous studies [5,6], who have suggested that Grape-associated microbial biogeography is non-randomly associated with regional and varietal across multiscale viticultural zones. The unique OTUs observed in fungal communities of each region and each grape varietal in SA and AST is particularly important since these unexplored fungal species may hold some potential for further application in local wine industries.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This observation suggests that each vineyard has fungal species which are the potential fungal signature of that region. Our result is in agreement with previous studies [5,6], who have suggested that Grape-associated microbial biogeography is non-randomly associated with regional and varietal across multiscale viticultural zones. The unique OTUs observed in fungal communities of each region and each grape varietal in SA and AST is particularly important since these unexplored fungal species may hold some potential for further application in local wine industries.…”
Section: Resultssupporting
confidence: 94%
“…In order to remain competitive in the global market, it is crucial to produce wines with a unique aromatic profile that reflect the 'terroir' from which they originate. Previous studies showed that grape microbiota exhibit regional patterns ('terroir') which contribute significantly to the quality of wine [5,6]. However, most studies have evaluated the grape associated microbiota in different regions/ vineyards of the same country whereas the comparative analysis of grape microbiota cultivated in different vineyards of two different countries has not been undertaken previously.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a prerequisite that the raw materials were not cleaned, as a site‐specific microflora grows on the surface of fruits and fish . This procedure can also be used in some cases for fermenting foods such as yogurt, cheese and wine, because these products are normally manufactured by applying a specific microbial starter culture . In this course, microbial fingerprinting allows the taxonomic classification of bacterial strains.…”
Section: Methodsmentioning
confidence: 99%
“…This may prevent us from formulating adequate land-use strategies for the conservation of biodiversity, sustainable viticulture, and the development of biotechnological solutions for the wine industry. It is also important to the wine industry to understand how agricultural management affects the microbial community of grapevines because grapevine microorganisms can affect the production of healthy grapes (Barata, Malfeito-Ferreira, & Loureiro, 2012;Pinto & Gomes, 2016) and wine quality (Bokulich et al, 2016;Knight, Klaere, Fedrizzi, & Goddard, 2015;Mezzasalma et al, 2017). The natural phyllosphere bacteria of the grapevine are likely to be highly resilient to agricultural treatments; studies have shown that differences in management, including chemical fungicides (Perazzolli et al, 2014), biological control (Perazzolli et al, 2014), and conventional, organic and biodynamic systems (Kecskeméti, Berkelmann-Löhnertz, & Reineke, 2016), do not affect bacterial diversity indices.…”
mentioning
confidence: 99%